Lung Ultrasound Predictive Value in Patients with Acute Heart Failure - Petrosyan, Harutyun; Manucharyan, Anush; Iusupbekova, Begimai; Terenik, Anna; Akulov, Pavel; Ghazaryan, Norik (Cardiology and Cardiovascular Medicine, 2025)
Acute heart failure (AHF) is a leading cause of hospitalization globally and is associated with high rates of early readmission and mortality [1]. Pulmonary congestion due to elevated cardiac filling pressures is a hallmark of AHF [2,6], and its timely assessment is critical for guiding therapy and improving outcomes. Traditional tools such as physical examination and chest radiography often fall short in detecting pulmonary congestion early and accurately [2,7]. Lung ultrasound (LUS), particularly through the identification of B-lines— vertical reverberation artifacts indicating extravascular lung water—has emerged as a rapid, non-invasive, and reliable alternative [3,8]. While the diagnostic role of LUS in heart failure (HF) is well established [1,3,8], its prognostic utility, especially in the early phase of AHF, remains underexplored. This study aimed to evaluate whether early B-line assessment using LUS can predict short- and long-term outcomes in patients with acute HF.